THE IMPORTANCE OF PUBLICIST GENRES IN COVERING THE IMPLEMENTATION OF THE LAW "ON THE STATE LANGUAGE" - Shakhobiddin Musaev (Modern American Journals, 2025)
This article discusses the role of journalism in the implementation of the Law of the Republic of Uzbekistan "On the State Language", the importance of journalistic genres in covering existing problems.
Keywords: State language, law, journalism, publicism, news, analytical genres, article, interview.